Age related human T cell subset evolution and senescence - Li, Mingde; Yao, Danlin; Zeng, Xiangbo; Kasakovski, Dimitri; Zhang, Yikai; Chen, Shaohua; Zha, Xianfeng; Li, Yangqiu; Xu, Ling (Immunity & ageing, 2019)
T cells are fundamental effector cells against viruses and cancers that can be divided into different subsets based on their long-term immune protection and immediate immune response effects. The percentage and absolute number of these subsets change with ageing, which leads to a reduced immune response in older individuals. Stem cell memory T cells (T SCM ) represent a small population of memory T cells with enhanced proliferation and differentiation properties that are endowed with high potential for maintaining T cell homeostasis. However, whether these cells change with ageing and gender remains unknown. Here, we assayed the distribution of T SCM and other T cell subsets in peripheral blood from 92 healthy subjects (44 females and 48 males) ranging from 3 to 88 years old by flow cytometry. We found that CD4+ and CD8+ T SCM in the circulation have relatively stable frequencies, and the absolute number of CD8+ T SCM decreased with age; however, the ratio of T SCM to the CD4+ or CD8+ naïve population increased with age. Unlike the obvious changes in other T cell subsets with age and gender, the stable level of T SCM in peripheral blood may support their capacity for sustaining long-term immunological memory, while their importance may increase together with ageing.